The Residual Innate Lymphoid Cells in NFIL3-Deficient Mice Support Suboptimal Maternal Adaptations to Pregnancy - Boulenouar, Selma; Doisne, Jean-Marc; Sferruzzi-Perri, Amanda; Gaynor, Louise M.; Kieckbusch, Jens; Balmas, Elisa; Yung, Hong Wa; Javadzadeh, Shagayegh; Volmer, Léa; Hawkes, Delia A.; Phillips, Keli; Brady, Hugh J.M.; et al. (Frontiers in Immunology, 2016)
Uterine NK cells are innate lymphoid cells (ILC) that populate the uterus and expand during pregnancy, regulating placental development and fetal growth in humans and mice. We have recently characterized the composition of uterine ILCs (uILCs), some of which require the transcription factor NFIL3, but the extent to which NFIL3-dependent cells support successful reproduction in mice is unknown. By mating Nfil3−/− females with wild-type males, here we show the effects of NFIL3 deficiency in maternal cells on both the changes in uILCs during pregnancy and the downstream consequences on reproduction. Despite the presence of CD49a+Eomes− uILC1s and the considerable expansion of residual CD49a+Eomes+ tissue-resident NK cells and uILC3s in pregnant Nfil3−/− mice, we found incomplete remodeling of uterine arteries and decidua, placental defects, and fetal growth restriction in litters of normal size. These results show that maternal NFIL3 mediates non-redundant functions in mouse reproduction.